A review of agricultural waste activated carbon and effect on adsorption parameters - Mohammad Razi, Mohd Adib; Mohd Hishammudin, Mimi Nur Attahirah; Abd Rahim, Muhammad Amirza; Mohd Salleh, Nur Aqila Hani (Inderscience Publishers, 2018)
Activated carbon is widely used in industrial wastewater treatment operation because of the effectiveness in removing the dye. As the conventional activated carbon on market nowadays is expensive, lots of research was done on agricultural materials to replace the activated carbon. Sugarcane bagasse is listed as one of the agricultural material alternatives. This review compiles the characterisation of sugarcane bagasse and several agricultural wastes-based activated carbon including proximate analysis, ultimate analysis, and activated carbon surface characteristic used to remove dye in textile wastewater. Nevertheless, the adsorption parameters are the main focus as it affecting the removal of dye. The expansion review regarding activated carbon performance implies that dye removal efficiency depends on the amount of adsorbent dosage, contact time, pH solution, dye concentration applied during the adsorption process. This review shows the need of thoughtful information on adsorption parameters with an expanded list of various types of agricultural-based activated carbon and various dye removal.